PERBANDINGAN PENYULUHAN DAN BUKU SAKU TERHADAP PENGETAHUAN REMAJA TENTANG HIV/AIDS - Sri Wahyuni; Flora Niu; Marlindah Marlindah (JKM (Jurnal Kebidanan Malahayati), 2021)
ABSTRACT COMPARISON OF COUNSELING AND POCKET BOOK TO TEENS KNOWLEDGE ABOUT HIV / AIDS   Background :The incidence of HIV / AIDS continues to increase every year. In the city of Jayapura, data from SIHA in 2018 for vulnerable people aged 15-19 years were 83 people with HIV / AIDS.Purpose To determine the comparison of counseling and pocket books on adolescent knowledge about HIV / AIDS in SMA Negeri 01 Abepura Jayapura. Methods: This research method is quantitative using a Quasi Experimental research design. The approach used in this study is non-randomized pre-test - posttest with control group design, a population of 1,537 people was taken by purposive sampling method, obtained 30 respondents. Data were collected by filling out a questionnaire before and after the intervention (counseling and pocket books). Data analysis using Independent t test and Paired t test.Result : there was a difference in the level of knowledge in the pre-test and post-test for the experimental group with counseling with a p value of 0.000 (<0.05), there was a difference in the level of knowledge between the pre and post test for the control group and the pocket book with a p value of 0.000 (<0, 05) there is a difference in the increase in the knowledge value of the extension group and pocket books with a p value of 0.006 (<0.05), and what is more effective is the extension because the mean value of the extension group is larger.Conclusion Extension is more effective in increasing knowledge.Suggestion counseling can be applied to increase knowledge about HIV / AIDS in adolescents at SMA 1 Abepura  Words: HIV / AIDS, knowledge, counseling, pocket books   ABSTRAK                 Latar belakang : Angka kejadian HIV/AIDS terus meningkat setiap tahunnya. Di kota Jayapura, data dari SIHA pada tahun 2018  untuk rentan umur 15-19 tahun sebanyak 83 penderita HIV/AIDS.Tujuan Untuk mengetahui perbandingan penyuluhan dan buku saku terhadap pengetahuan pada remaja tentang HIV/AIDS di SMA Negeri 01 Abepura Jayapura.Metode : Penelitian ini kuantitatif dengan menggunakan desain penelitian Quasi Eksperimen. Pendekatan yang dilakukan pada penelitian ini adalah non randomized pre test - post test with control group design, populasi sebanyak 1.537 orang diambil dengan metode purposive sampling, didapatkan responden dengan jumlah 30 orang. Data dikumpulkan dengan pengisian kuesioner sebelum dan sesudah pemberian intervensi (penyuluhan dan buku saku). Analisis data menggunakan uji Independen t test dan Paired t test.Hasil: Penelitian terdapat perbedaan tingkat pengetahuan pre test dan post test untuk kelompok eksperimen dengan penyuluhan dengan p value 0,000 (<0,05), terdapat perbedaan tingkat pengetahuan antara pre dan post test untuk kelompok kontrol dengan buku saku dengan p value 0,000 (<0,05) terdapat perbedaan kenaikan nilai pengetahuan kelompok penyuluhan dan buku saku dengan p value 0,006 (<0,05), dan yang lebih efektif adalah penyuluhan karena nilai mean kelompok penyuluhan lebih besar.Kesimpulan : Penyuluhan lebih efektif dalam meningkatkan pengetahuan.Saran penyuluhan dapat diterapkan untuk meningkatkan pengetahuan mengenai HIV/AIDS pada remaja di SMA 1 AbepuraKata Kunci: HIV/AIDS, pengetahuan, penyuluhan, buku saku